Ecologically sustainable cassava plant protection (EScaPP): annual report - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 1994)
Cassava, a tropical root crop, is increasingly important as a food and income source for the rapidly expanding rural and urban populations in Africa and Latín America, playing a key role in poverty alleviation. The storage roots are processed, usually by women, into various food products and animal feed ingredients for domestic use and export. Cassava is also an emergency food reserve under adverse environmental and socio-political conditions when most other crops fail. However, pests1 and poor agronomic practices reduce cassava crop production by an estimated 50%. The losses affect more than 300 million of the world's poor, including as many as 43 million malnourished children. The diversity and geographic range of cassava pest constraints require comprehensive regional R&D approaches to develop and implement holistic intervention technologies that improve cassava plant health, increase yields and ensure good production environments. A previous UNDP-sponsored project "Ecologically Sustainable Cassava Plant Protection in South America and Africa" (known as ESCaPP in Africa and PROFISMA in South America) executed by IITA and CIAT in collaboration with the NARS in Benin, Ghana, Cameroon and Nigeria in Africa and Brazil in Latín America made significant achievements in this regard. However, there remains the need to address further plant protection constraints to cassava production at regional and national levels in new regions, and on prioritized constraints in previously served regions.